2020
DOI: 10.1088/1748-0221/15/08/t08005
|View full text |Cite
|
Sign up to set email alerts
|

Calibration method and photon flux influences tiled flat-panel photon counting detector image uniformity in computed tomography

Abstract: The aim of this study is to compare how different calibration methods influence the image quality of photon-counting detector computed tomography (PCD-CT) at high and low photon fluxes. We investigate the performance of flat-field correction, signal-to-equivalent thickness calibration (STC), and polynomial correction (PC) methods using polymethyl methacrylate (PMMA) and iron as calibration materials. Two different cylindrical imaging phantoms containing contrast targets were scanned: an agar phantom and a phan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This effect was observed in our system as well. Inkinen et al 43 . also reported that these issues are exacerbated at high‐flux conditions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This effect was observed in our system as well. Inkinen et al 43 . also reported that these issues are exacerbated at high‐flux conditions.…”
Section: Discussionmentioning
confidence: 97%
“…This effect was observed in our system as well. Inkinen et al 43 also reported that these issues are exacerbated at high-flux condi-tions. It is unclear whether or not these are limitations of current PCD technology that may be overcome with further technological development, or if they are fundamental limitations that will persist into the next generation of PCD technology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, high-resolution photon counting detector (PCD) CT improved the coronary stent lumen visibility compared to dual-energy CT (DECT), and VMIs enabled estimation of iodine and gadolinium concentration estimation from the stent region (Symons et al 2018). In PCD-CT, the beam hardening artefacts are more prominent in the low energy images (Inkinen et al 2020), and in cardiac imaging, the surrounding bony structures i.e. ribs and spine cause beam hardening in low energy PCD-CT images if not corrected.…”
Section: Introductionmentioning
confidence: 99%
“…ribs and spine cause beam hardening in low energy PCD-CT images if not corrected. One approach to reduce beam-hardening artefacts is to use VMIs (Kuchenbecker et al 2015, Inkinen et al 2020.…”
Section: Introductionmentioning
confidence: 99%